Bots, Cyborgs and WhatsAppers: Human and Non-Human Actors in Brazilian Digital Political Groups - Bittencourt , Geraldo (2022)
This article seeks to answer the question: how can members of digital political groups be characterized when the existence of human and non-human actors in the environment is admitted? For this, an exploratory research was carried out with 1,040 members of Brazilian political WhatsApp groups between October 30, 2020 and November 29, 2020. After collecting and analyzing the results, it was noticed that the groups are formed mostly by WhatsAppers, who are the organic members, but the presence of bots and cyborgs is also noticeable. The performance of these fully or partially automated accounts is linked to the sharing of unfavorable messages to opponents or content that praises politicians who enjoy the preference of space.